On the spider genus Naubolus Simon, 1901 (Araneae: Salticidae) - Rubio, Gonzalo Daniel (2024)
As a part of a general revision of the South American Dendryphantini, type materials of several taxa have been examined. Certain inconsistencies regarding the species composition of the genus Naubolus Simon, 1901 have been observed. In order to resolve these inconsistencies the type series of two Naubolus species have been studied. The unknown male of Naubolus posticatus Simon, 1901 is described, and N. simplex Mello-Leitão, 1946 is redescribed; yet, a provisional species group with distinctive characters within the genus is proposed.